O currículo de matemática nos anos finais do ensino fundamental: um olhar para o referencial curricular em Caçapava do Sul/RS - (:unkn) unknown (Universidade Federal do Pampa, 2016)
A number of legal documents guide classroom practice. In addition to these documents, in Rio Grande do Sul (RS), in particular, a proposal, called Lessons from Rio Grande, constitutes the Curricular Reference that guides teachers and the school. Thus, the present work aimed to identify the aspects involved in the process of implementation of the proposal that concerns the final grades of the Elementary School of RS by Mathematics teachers, in the city of Caçapava do Sul. The specific objectives were: to investigate the course of elaboration of the Referential until its implementation; find out how this document was presented to teachers; and, characterize the continuing education offered to teachers to support the implementation of the Curricular Reference (CR). The data production occurred by reading the School and RC Teaching Plans, as well as conducting a semi-structured interview with some mathematics teachers of the final grades of elementary school in public schools (state and municipal) in the city of Caçapava do Sul. Data analysis was performed through Discursive Textual Analysis. The results are presented under three categories, namely: (i) lack of knowledge of the Curriculum Framework; (ii) textbook as a teaching plan and (iii) discrepancy between the continuing education offered and the teacher's need. It is signaled that continuing education does not meet the needs of teachers, which can be pointed as one of the causes of their ignorance of the Curricular Reference. Thus, the curriculum modeled by them, which should guide their classroom practice, does not meet the requirements of the Curriculum Framework, on the contrary, can be understood as the contents indicated by the chosen textbook, not considering, in general, what The State Department of Education studied and rated it as important for student learning.
Keywords: Currículo; Matemática; Referencial curricular; CNPQ::CIENCIAS EXATAS E DA TERRA